Growth of triploid and diploid Acacia clones in three contrasting environments in Viet Nam - Bon, P.V.; Harwood, C.E.; Nghiem, Q.C.; Thinh, H.H.; Son, D.H.; Chinh, N.V. (Informa UK Limited, 2020)
We assessed the growth and adaptability of triploid acacia clones in comparison with commercially planted diploid clones of the same taxa to age three years at three contrasting sites in north, central and south Viet Nam. Application of phosphorus fertiliser at planting gave a growth response only in the trial in central Viet Nam. One triploid Acacia hybrid (Acacia auriculiformis × mangium) clone was constantly the best performer in all sites, achieving mean annual increments at three years of 30.1, 26.6 and 32.1 m3 ha−1 in northern, central and southern Viet Nam, respectively. Two other triploid hybrid clones outperformed the diploid controls in southern Viet Nam. A single triploid A. auriculiformis clone and two diploid clones of this species grew much more slowly. Triploid Acacia hybrid clones had a lower incidence of Corticium salmonicolor (pink disease) and Ceratocystis disease symptoms than did diploid hybrid clones. The wind-firmness of triploid Acacia hybrid clones was comparable with or better than the diploid hybrid clones. Triploid breeding offers a promising new pathway in the development of improved Acacia planting material.